2022
DOI: 10.21203/rs.3.rs-1355792/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulation Based Clinical Skill Training; A Need Of Time

Abstract: Objective: To explore the perception and attitude about simulation-based learning (SBL) of clinical skills in undergraduate medical students.Place and Duration of Study: College of Medicine, Princess Noura bint Abdulrehman university; Riyadh, Saudi Arabia, from March to September 2019.Method: A pre-tested structured self-administered questionnaire was used to collect the data about student’s perception about simulation-based learning. Informed written consent was taken from the students. Data analysis was done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Similar study found that most of the students (81.6%) strongly believed that simulation support can help to develop their clinical skills. This finding is quite similar to the findings of present study 5 .…”
Section: Quantitative Partsupporting
confidence: 94%
“…Similar study found that most of the students (81.6%) strongly believed that simulation support can help to develop their clinical skills. This finding is quite similar to the findings of present study 5 .…”
Section: Quantitative Partsupporting
confidence: 94%